What information can change the attitude of teachers toward the human papillomavirus vaccine?. Issue 4 (14th February 2018) - Kamada, Masaharu; Inui, Hiroaki; Kagawa, Tomohiro; Mineda, Ayuka; Tamura, Takao; Fujioka, Tomohito; Motoki, Takahiro; Hirai, Hiroki; Ishii, Eiichi; Irahara, Minoru
Abstract: Aim: We conducted a self‐administered survey on the perception of teachers toward human papillomavirus (HPV) vaccine to determine the ways to increase their willingness to encourage its use. Methods: Answers were obtained both prior to and after having the teachers read five brief information articles: (i) cervical cancer knowledge, (ii) vaccine knowledge, (iii) result of a survey in Nagoya, (iv) news report of the World Health Organization statement and (v) articles written by Dr Muranaka, a journalist. Results: Most of the respondents (180/247) did not know about the natural history of cervical cancer. Only 36% knew that HPV is the cause of cervical cancer, although 63% knew that HPV vaccine would prevent cervical cancer. Few respondents had knowledge regarding adverse events following immunization and the survey results from Nagoya. Among those who were initially negative for the HPV vaccine, only 43% revealed that they fully understood its safety and only 29% reversed their opinion to recommend vaccination to their daughters and/or students, even after reading our informational material. The most useful information for changing their attitudes was to increase their understanding of vaccines and informing them about Nagoya city survey results. They mostly wanted a proof of the preventive effects of the vaccine on cervical cancer in Japan. Conclusion: Gynecologists and pediatricians must proactively communicate accurate scientific information to the government and the media to spread awareness among people in Japan. Also, we must try to demonstrate the capabilities of this vaccine to prevent cervical cancer and/or its precancerous lesions.